PERBAIKAN TATA LETAK GUDANG BAHAN PENOLONG DENGAN MENGGUNAKAN METODE DEDICATED STORAGE PADA PT. X - Aden Mas Melia, (2020)
PT. X is a company engaged in the production of fertilizers where the final products are Subsidized and Non-Subsidized Urea Fertilizers, Subsidized and Non-Subsidized ZA Fertilizers. PT. X has an auxiliary materials warehouse to store the materials that will be supplied to production department. In the process of storing auxiliary materials in the warehouse, the company faces a problem that the placement of material in the warehouse is irregular and the difficulty of operator and material handling that used to place and search the goods when the goods is ready to be shipped. Therefore, it is necessary to improve the layout of auxiliary materials warehouse by using the Dedicated Storage Method to obtain specific and efficient materials positions in the warehouse. By using the Dedicated Storage Method, the storage slot needed to store all materials is 127 pallets. Obtained the highest activity material, ZA Subsidized Sack with T/S value of 3.444. The Non-Subsidized ZA Sack material has the lowest activity with T/S value 1.207. The researcher also made a simulation with Promodel and it produced an output time of material handling when the actual condition was 2.01 hours/day. While the time of material handling in the proposed layout is 1.06 hours/day. There was a reduction in travel time by 4.22%. Calculation of the material handling distance in the actual layout is 4683,894 m/month, while the material handling distance in the proposed layout is 4375,439 m/month.